ANALISIS PELAYANAN AKADEMIK DALAM PERSPEKTIF NEW PUBLIC SERVICE FAKULTAS VOKASI UNIVERSITAS BRAWIJAYA MALANG - Mohammad Bisri (Jurnal Administrasi Publik, 2023)
As one of the best universities in Indonesia, Universitas Brawijaya is also not free from service problems-especially academic services to students. For example, these problems can be found in the Faculty of Vocational Studies, Universitas Brawijaya. Based on the findings in the field, shows that there are still many services provided by the Faculty of Vocational Studies that are not maximized, such as the lack of precise and accurate explanations regarding the output of the services provided. The existence of these cases is essential to analyze academic services to improve academic services. The research method used is a qualitative method with a descriptive approach. The results showed that the ten NPS indicators: Tangible, Reliability, Responsiveness, Competence, Courtesy, Credibility, Security, Access, Communication, and Understanding Customer are not yet optimal because problems such as employee attitudes, employee ratios, and employee communication are still not by student expectations. To create optimal service, academic staff, and students must create a sense of shared responsibility to create ideal service.